Спасти лето: [роман] / Кристи Кострова - Кострова Кристи (Звезда Рунета, 2018)
Экземпляры: Атабаевская с/б (20240130) / Инвентарный номер: 47963 / Цена: / Авт.знак: К 72 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44